Edukasi Latihan Core Stability terhadap Nyeri Punggung Bawah pada Pembatik Kajang Lako Kota Jambi - Putra Hadi; Wanti Hasmar (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The batik makers tend to be in a long sitting position followed by the unergonomic position of the batik makers, the way they work, all of which still use the manual method, will certainly cause a lot of complaints or skeletal muscle disorders. One of the triggering factors for these mechanical disorders is prolonged sitting according to research showing about 39.5-60% of adults experience low back pain due to prolonged sitting for 1.5 hours - 5 hours. One of the jobs at risk for NPB is batik. Batik craftsmen usually have a static nature of work that is carried out within 8 hours per day in a sitting condition. Static muscle contractions for 8 hours in a sitting condition can increase muscle and spinal ligament tension. Community service activities were carried out in June 2022 with the method of discussing and delivering materials and leaflets related to the bad ergonomic effects that lead to lower back pain and demonstrating core stability exercises. This community service aims to be used as a source of knowledge for mothers of batik craftsmen at the Kajang Lako batik studio across the city of Jambi. The results of the evaluation through the question and answer session were that the batik craftsmen had understood how to practice core stability correctly and were able to do it independently.